Pembelajaran Pendidikan Agama Islam Berbasis Kurikulum Pendidikan Karakter Dalam Menumbuhkan Kecerdasan Emosional Siswa SMK Bina Harapan Sumedang - Mauzifa Mauzifa; Andri Irawan; Asep Nursobah (Penerbit Hellow Pustaka, 2024)
The integration of character education in PAI learning at SMK Bina Harapan, Sumedang, aims to foster students' emotional intelligence. This research uses a qualitative method with a case study design, the researcher as the main instrument, with interview, observation, and documentation methods. Data were analyzed descriptively qualitatively by following the three steps of Miles and Huberman: data reduction, data presentation, and conclusion drawing. Data validation was done through triangulation. The results showed that the implementation of character education-based PAI learning is based on the implementation of the character education curriculum by SMK Bina Harapan, the curriculum is designed with a philosophical foundation to equip students as human resources who are ready to face the demands of the labor market and modern culture. The curriculum integrates character education that is effective in fostering students' emotional intelligence through the PAI learning process. Through Goleman's five aspects of emotional intelligence approach (self-awareness, self-regulation, Motivation, empathy, and Social skills), students are guided to manage emotions, increase Motivation, and strengthen Social skills. Strategies such as journaling, reflection, group discussions with reflective and inclusive methods, and counseling guidance help shape positive character and create a learning environment that supports emotional and social development, as well as having strong moral integrity in accessing and using technology, which can provide positives (community contribution, creating innovative solutions, building social networks, and encouraging ethical values in the use of technology), become the main hope that digital progress towards students does not in the least sacrifice human values that undermine morality.